2017
DOI: 10.1016/j.pnpbp.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21: Expression in oligodendrocytes and correlation with low myelin mRNAs in depression and alcoholism

Abstract: MiR-21 is a microRNA implicated in cancer, development, and cardiovascular diseases and expressed in the central nervous system (CNS), especially after injury. However, the cellular expression of miR-21 in the adult CNS has not been clearly established either in mice or human subjects, while its alteration in psychiatric disorders is unknown. MiR-21 expression was characterized in reporter mice expressing β–galactosidase (LacZ) under the endogenous miR-21 promoter (miR-21/LacZ). Brain co-localization of miR-21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 67 publications
(84 reference statements)
3
41
0
Order By: Relevance
“…These reductions are particularly significant in chronic alcoholics with cirrhosis as compared to non-alcoholic controls or to non-cirrhotic alcoholics (Lewohl et al, 2005 ), suggesting that nutritional deficiencies or metabolic toxicity, possibly interacting with direct ethanol effects, strongly deplete the expression of myelin components in alcoholics, at least as assessed in studies that include GM in the probed tissue. In contrast, in a recent study from our laboratory, we used samples only from the WM adjacent to cortical area 47 (orbitofrontal cortex) in chronic alcoholics, and observed that mRNA levels for myelin proteins PLP, MAG and MOG and other oligodendrocyte markers were markedly lower than in controls, although the levels of MBP mRNA were not changed (Miguel-Hidalgo et al, 2017 ). Since cirrhosis had not been diagnosed in most subjects of our study, these results suggest that the effects of prolonged alcohol abuse in some regions of WM may occur without cirrhosis and be different from those when GM is included.…”
Section: Molecular Pathology Of Oligodendrocytes In Alcohol Use Disormentioning
confidence: 77%
See 3 more Smart Citations
“…These reductions are particularly significant in chronic alcoholics with cirrhosis as compared to non-alcoholic controls or to non-cirrhotic alcoholics (Lewohl et al, 2005 ), suggesting that nutritional deficiencies or metabolic toxicity, possibly interacting with direct ethanol effects, strongly deplete the expression of myelin components in alcoholics, at least as assessed in studies that include GM in the probed tissue. In contrast, in a recent study from our laboratory, we used samples only from the WM adjacent to cortical area 47 (orbitofrontal cortex) in chronic alcoholics, and observed that mRNA levels for myelin proteins PLP, MAG and MOG and other oligodendrocyte markers were markedly lower than in controls, although the levels of MBP mRNA were not changed (Miguel-Hidalgo et al, 2017 ). Since cirrhosis had not been diagnosed in most subjects of our study, these results suggest that the effects of prolonged alcohol abuse in some regions of WM may occur without cirrhosis and be different from those when GM is included.…”
Section: Molecular Pathology Of Oligodendrocytes In Alcohol Use Disormentioning
confidence: 77%
“…Increased miRNAs include some targeting major myelin proteins such as PLP1 and CNPase as well as transcription factor C11ORF9, a regulator of myelin formation. In our recent work, we found that miR-21, high in oligodendrocytes, was strongly and positively correlated with decreased PLP1 miRNA (which is not a direct target of miR-21; Miguel-Hidalgo et al, 2017 ). The networks and pathways regulated by differentially expressed miRNAs in human alcoholics and mice are very highly enriched in oligodendrocytes and astrocytes, some of them exclusively for each cell type (Nunez et al, 2013 ).…”
Section: Epigenetic Changes In Oligodendrocytes and Astrocytes In Audmentioning
confidence: 85%
See 2 more Smart Citations
“…Most of these miRNAs are contained in common miRNAs. For example, Hsa-miR-21 is not only involved in the alterations of white matter in depression and alcoholism [ 26 ], but it also plays a key role in the pathogenesis of GBM and can be used as a biomarker for the diagnosis and treatment of GBM patients [ 27 ]. The miRNAs were found to be closely related to the abnormal expression of CD3, CD14, CD19, and CD56 in immune cells category.…”
Section: Discussionmentioning
confidence: 99%